catena-Poly[[dichloridozinc(II)]-μ-1,4-bis(pyridin-2-ylmethoxy)benzene-κ(2) N:N′] - Liu, Ying (International Union of Crystallography, 2011)
In the title compound, [ZnCl(2)(C(18)H(16)N(2)O(2))](n), the Zn(II) ion is tetrahedrally coordinated by two Cl atoms and by two N atoms from different 1,4-bis(pyridin-2-ylmethoxy)benzene ligands. The ligand shows a non-planar configuration, in which the dihedral angles between the two terminal pyridine rings and the linking benzene ring are 7.86 (12) and 70.74 (11)°. The flexible ligand coordinates to the Zn(II) ions, generating an infinite chain propagating along [001].